Video-based measurement for transverse vibrations of moving catenaries in mine hoist using mean shift tracking - Jiannan Yao; Xingming Xiao; Hao Chang (Advances in Mechanical Engineering, 2015)
This work proposed a non-contact video-based measurement for transverse displacements of hoisting catenaries in mine hoist using mean shift tracking. Hoisting catenaries are typically moving cables making it impossible to use traditional methods. To obtain the transverse displacements of an arbitrary point in the hoisting catenary, a guide line that was perpendicular to the hoisting catenaries was inserted in the sequential images. Through tracking the dynamic intersection area by mean shift algorithm and then recording the location of the tracker, the transverse vibration displacements of the selected point in the hoisting catenary can be easily obtained. A theoretical model of transverse vibration of a catenary was established, and model validation was then conducted confirming the reasonability and applicability of the proposed method. Eventually, a laboratory experiment was also conducted and then confirmed the accuracy of the proposed method. This work is perfectly suitable for the measurement of moving cable vibration.